Some Results on Fibrewise Topological Spaces - Yousif, Y.Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we define and study new concepts of functions on fibrewise  topological spaces  over  B namely,  fibrewise  weakly  (resp., closure, strongly) continuoac; funttions which are analogous of weakly(resp., closure,   strongly)   continuous  functions   and  the  main  result is   : Let  O'fl  : z  Y is weakly (resp.â€¢weakly, closure,  strongly,  continuous). Also, we define  and study  the concepts   fibrewise  ro-closed  (resp.,  roÂ·coclosed, (i}Â·biclosed, IDÂ·open, co-coopen, roÂ·biopen) topological  spaces over B which is similar  of definition of fibrewise c1osed (resp., open) topological  spaces over B; also  we state  and prove  several  propositions concerning   with  these concepts.